Follow the Moon Home : a Tale of One Idea, Twenty Kids, and a Hundred Sea Turtles - Cousteau, Philippe 1980-; Hopkinson, Deborah; So, Meilo (San Francisco, California : Chronicle Books, 2016)
"A book about loggerhead sea turtles, and a girl's attempts to help save their babies from man-made light"--
Keywords: Loggerhead turtle -- Juvenile literature. -- Infancy; Rare reptiles -- Juvenile literature; Child environmentalists -- Juvenile literature; Nature conservation -- Juvenile literature. -- Citizen participation; Loggerhead turtle -- Infancy; Rare reptiles; Environmentalists; Nature conservation -- Citizen participation